Conductive paste and multilayer substrate using the same
By reasonably proportioning solid and liquid epoxy resins, spherical high-melting and low-melting metal particles, curing agents and fluxes in the conductive paste, the shortcomings in the adhesiveness of the existing conductive paste are solved, and excellent effects of conductivity and adhesiveness are achieved.
Patent Information
- Application Number
- CN202380060702.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-01
- Filing Date
- 2023-08-30
- Publication Date
- 2025-04-01
AI Technical Summary
There is room for improvement in the adhesion of existing metallized types of conductive pastes.
A conductive paste containing 5 to 60 parts by mass of solid epoxy resin and 40 to 95 parts by mass of liquid epoxy resin, is used, and a conductive paste containing 770 to 4300 parts by mass of spherical high-melting metal particles and 1510 to 5400 parts by mass of spherical low-melting metal particles, 10 to 150 parts by mass of curing agent and 30 to 200 parts by mass of flux.
It achieves excellent conductivity and adhesiveness, and is suitable for hole filling of multilayer substrates.
Smart Images

Figure CN119744424A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive paste and a multilayer substrate using the conductive paste. Background Art
[0002] As a conductive paste for filling holes in a substrate, there is known a conductive paste of a type in which metal particles are in contact with each other to obtain conductivity. Alternatively, there is also a type in which conductive metal particles are mixed with high-melting-point conductive metal particles and low-melting-point metal particles are mixed, or a type in which conductive metal particles are only composed of low-melting-point metal particles and are connected to each other (metallized) by heating to exhibit conductivity. Hereinafter, such a metallized type is sometimes referred to as a "metallized type".
[0003] As a metallization type conductive paste, for example, there is known a conductive paste described in Patent Document 1. This conductive paste contains 200 to 1800 parts by weight of metal powder (B), 3 to 20 parts by weight of a curing agent (C), and 3 to 15 parts by weight of a soldering flux (D) with respect to 100 parts by weight of a resin component (A) composed of 20 parts by weight or more of an epoxy resin having an epoxy equivalent in the range of 200 to 600 and a hydrolyzable chlorine concentration of less than 200 ppm and less than 80 parts by weight of a resin other than the epoxy resin, and having a total hydrolyzable chlorine concentration of less than 1000 ppm, wherein the metal powder is composed of two or more metals including at least one low melting point metal having a melting point of 180° C. or less and at least one high melting point metal having a melting point of 800° C. or more.
[0004] However, conventional metallization-type conductive pastes have room for further improvement in terms of adhesiveness.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2008-108629
[0008] Patent Document 2: Japanese Patent Application Publication No. 2017-152221
[0009] Patent Document 3: Japanese Patent Application Publication No. 2014-220238 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a conductive paste having both excellent conductivity and adhesiveness.
[0012] It should be noted that Patent Documents 2 and 3 describe conductive pastes using a liquid epoxy resin and a solid epoxy resin in combination, but neither document is a metallization type conductive paste.
[0013] Solutions for solving problems
[0014] The present invention includes the following embodiments.
[0015] [1] A conductive paste comprising 770 to 4300 parts by mass of spherical high-melting-point metal particles (B) having a melting point of 800° C. or higher, 1510 to 5400 parts by mass of spherical low-melting-point metal particles (C) having a melting point of 240° C. or lower, 10 to 150 parts by mass of a curing agent (D), and 30 to 200 parts by mass of a soldering flux (E), relative to 100 parts by mass of a binder component (A) comprising 5 to 60 parts by mass of a solid epoxy resin and 40 to 95 parts by mass of a liquid epoxy resin in a total amount not exceeding 100 parts by mass.
[0016] [2] The conductive paste according to [1], wherein the spherical high-melting-point metal particles (B) include at least one selected from the group consisting of silver particles, silver-coated copper particles, and silver-coated copper alloy particles.
[0017] [3] The conductive paste according to [1] or [2], wherein the spherical low-melting-point metal particles (C) are composed of an alloy of two or more selected from the group consisting of tin, lead, bismuth, and indium.
[0018] [4] The conductive paste according to any one of [1] to [3], wherein the liquid epoxy resin includes at least one selected from the group consisting of bisphenol epoxy resins, rubber-modified epoxy resins, and glycidyl ether epoxy resins.
[0019] [5] The conductive paste according to any one of [1] to [4], wherein the mass ratio (B) / (C) of the spherical high-melting-point metal particles (B) to the spherical low-melting-point metal particles (C) is 0.25 to 2.
[0020] [6] A multilayer substrate comprising a plurality of conductive layers and insulating layers interposed between the plurality of conductive layers, wherein holes penetrating the insulating layers are filled with a conductive paste solidified material, and the conductive layers in contact with both surfaces of the insulating layers are electrically connected to each other via the conductive paste solidified material, wherein the conductive paste solidified material is a solidified material of the conductive paste described in any one of [1] to [5].
[0021] Effects of the Invention
[0022] According to the conductive paste of the present invention, excellent conductivity and adhesiveness can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic cross-sectional view showing a method for manufacturing a multi-layer substrate according to one embodiment of the present invention.
[0024] Figure 2 It is a schematic cross-sectional view showing another method for manufacturing a multi-layer substrate according to one embodiment of the present invention. DETAILED DESCRIPTION
[0025] Hereinafter, embodiments of the present invention will be described in more detail.
[0026] The conductive paste of the present embodiment comprises 770 to 4300 parts by mass of spherical high-melting-point metal particles (B) having a melting point of 800° C. or higher, 1510 to 5400 parts by mass of spherical low-melting-point metal particles (C) having a melting point of 240° C. or lower, 10 to 150 parts by mass of a curing agent (D), and 30 to 200 parts by mass of a soldering flux (E), relative to 100 parts by mass of a binder component (A) comprising 5 to 60 parts by mass of a solid epoxy resin and 40 to 95 parts by mass of a liquid epoxy resin in a total amount not exceeding 100 parts by mass.
[0027] Here, "solid epoxy resin" refers to an epoxy resin that does not have fluidity in a solvent-free state at room temperature (23°C). As a solid epoxy resin, as long as it contains an epoxy group in the molecule and is solid at room temperature (23°C), there is no particular limitation. As specific examples, trisphenol epoxy resin, trisphenol methane epoxy resin, bisphenol epoxy resin (such as bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin), naphthalene epoxy resin, biphenyl epoxy resin, terpene epoxy resin, phenol novolac epoxy resin, etc. can be cited. They can be used alone or in combination of two or more. In addition, the solid epoxy resin can be dissolved in a solvent for use.
[0028] In addition, "liquid epoxy resin" refers to an epoxy resin that has fluidity in a solvent-free state at room temperature (23°C). As a liquid epoxy resin, there is no particular limitation as long as it contains an epoxy group in the molecule and is liquid at room temperature (23°C). As specific examples, bisphenol epoxy resins (such as bisphenol A epoxy resins, bisphenol F epoxy resins), glycidylamine epoxy resins, glycidyl ether epoxy resins, rubber-modified epoxy resins, etc. can be cited. They can be used alone or in combination of two or more. Among these, as liquid epoxy resins, bisphenol epoxy resins, rubber-modified epoxy resins, and glycidyl ether epoxy resins are preferred, and a combination of bisphenol epoxy resins and rubber-modified epoxy resins is more preferred.
[0029] "Rubber-modified epoxy resin" refers to an epoxy resin in which a rubber component is dispersed in the above-mentioned liquid epoxy resin. Examples of the above-mentioned rubber component include polybutadiene rubber (BR), (poly)acrylate rubber (ACM), silicone rubber, butyl rubber (IIR), isoprene rubber (IR), chloroprene rubber (CR), nitrile rubber (NBR), styrene butadiene rubber (SBR), ethylene propylene rubber (EPR), etc. Among them, epoxy resin modified with NBR (NBR-modified epoxy resin) is preferred. The above-mentioned rubber component can be used alone or in combination of two or more.
[0030] The content of the solid epoxy resin in 100 parts by mass of the binder component is preferably 5 to 60 parts by mass, more preferably 10 to 55 parts by mass, and even more preferably 15 to 50 parts by mass. When the content of the solid epoxy resin is within the above range, excellent conductivity and adhesion are easily obtained.
[0031] In 100 parts by mass of the adhesive component, the content of the liquid epoxy resin is preferably 40 to 95 parts by mass, more preferably 45 to 90 parts by mass, and further preferably 50 to 85 parts by mass. In a more preferred embodiment, in 100 parts by mass of the adhesive component, the rubber-modified epoxy resin is preferably contained as the liquid epoxy resin in a ratio of 1 to 50 parts by mass, and more preferably in a ratio of 5 to 45 parts by mass. In addition, in 100 parts by mass of the adhesive component, the liquid epoxy resin other than the rubber-modified epoxy resin is preferably contained in a ratio of 10 to 90 parts by mass, and more preferably in a ratio of 10 to 40 parts by mass. When the content of the liquid epoxy resin is within the above range, excellent conductivity and adhesion are easily obtained.
[0032] The content ratio of the solid epoxy resin to the liquid epoxy resin is not particularly limited, and the mass ratio (solid / liquid) is preferably 0.05 to 1.5, more preferably 0.1 to 1.2. When the content ratio of the solid epoxy resin to the liquid epoxy resin is within the above range, excellent conductivity and adhesion are easily obtained.
[0033] The weight average molecular weight of the solid epoxy resin is not particularly limited, but is preferably 900 to 60000, more preferably 1000 to 55000, and further preferably 1200 to 50000. It should be noted that in this specification, the "weight average molecular weight" can be measured by gel permeation chromatography (GPC), and is a value calculated using a polystyrene-converted calibration curve using tetrahydrofuran as a mobile phase.
[0034] The weight average molecular weight of the liquid epoxy resin is not particularly limited, but is preferably 150 to 500, more preferably 180 to 450, and even more preferably 200 to 400.
[0035] The epoxy equivalent of the solid epoxy resin is not particularly limited, but is preferably 150 to 10,000 g / eq, more preferably 200 to 9,000 g / eq, and further preferably 250 to 8,000 g / eq.
[0036] The epoxy equivalent of the liquid epoxy resin is not particularly limited, but is preferably 90 to 500 g / eq, more preferably 100 to 450 g / eq, and further preferably 120 to 400 g / eq.
[0037] In this specification, "epoxy equivalent" is measured according to JIS K7236:2009.
[0038] The content of the spherical high melting point metal particles (B) having a melting point of 800° C. or higher is 770 to 4300 parts by mass, preferably 900 to 4000 parts by mass, and more preferably 1000 to 3800 parts by mass relative to 100 parts by mass of the binder component. When the content of the spherical high melting point metal particles (B) is within the above range, excellent conductivity is easily obtained.
[0039] As spherical high melting point metal particles (B), silver particles, silver-coated copper particles, silver-coated copper alloy particles, etc. can be cited. The silver-coated copper particles are not particularly limited as long as they have copper particles and a silver-containing layer covering at least a portion of the copper particles. The silver-coated copper alloy particles are not particularly limited as long as they have copper alloy particles and a silver-containing layer covering at least a portion of the copper alloy particles. The copper alloy particles contain 0.5 to 25% by mass of zinc and / or 0.5 to 30% by mass of nickel, and the remainder is composed of copper, and the remaining copper may contain unavoidable impurities. The content ratio of the silver-containing layer in the silver-coated copper particles and the silver-coated copper alloy particles is not particularly limited, and is preferably 4 to 24% by mass. The content of silver in the silver-containing layer is not particularly limited, and is preferably 90 to 100% by mass.
[0040] The average particle size of the spherical high melting point metal particles (B) is not particularly limited, but is preferably 0.5 to 20 μm, more preferably 1 to 10 μm. Here, in this specification, the "average particle size" refers to the particle size (primary particle size) at which the cumulative value of the particle size distribution obtained by laser diffraction scattering method is 50%.
[0041] The content of the spherical low-melting-point metal particles (C) having a melting point of 240° C. or less is 1510 to 5400 parts by mass, preferably 1600 to 5200 parts by mass, and more preferably 1900 to 5000 parts by mass, relative to 100 parts by mass of the binder component. When the content of the spherical low-melting-point metal particles (C) is within the above range, excellent conductivity is easily obtained.
[0042] As the spherical low-melting-point metal particles (C), metal particles composed of an alloy of two or more selected from the group consisting of tin (melting point: 231° C.), lead (melting point: 327° C.), bismuth (melting point: 271° C.), and indium (melting point: 156° C.) can be used.
[0043] The average particle size of the spherical low-melting-point metal particles (C) is not particularly limited, but is preferably 1 to 20 μm, and more preferably 2 to 10 μm.
[0044] The melting point of the spherical high melting point metal particles (B) is not particularly limited as long as it is 800°C or more. The melting point of the spherical high melting point metal particles (B) can be, for example, 800 to 1460°C. The melting point of the spherical low melting point metal particles (C) is not particularly limited as long as it is 240°C or less. The melting point of the spherical low melting point metal particles (C) can be, for example, 130 to 235°C.
[0045] The content ratio of the spherical high melting point metal particles (B) to the spherical low melting point metal particles (C) is preferably 0.25 to 2, more preferably 0.4 to 1.5 in terms of mass ratio ((B) / (C)).
[0046] The content of the curing agent (D) is 10 to 150 parts by mass, preferably 15 to 140 parts by mass, and more preferably 20 to 130 parts by mass relative to 100 parts by mass of the binder component. When the content of the curing agent (D) is within the above range, excellent conductivity and adhesion are easily obtained.
[0047] The curing agent (D) is not particularly limited, and an isocyanate curing agent, a cationic curing agent, or a phenolic curing agent can be used. These can be used alone or in combination of two or more.
[0048] As the isocyanate curing agent, for example, there can be mentioned lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated xylene diisocyanate; aromatic polyisocyanates such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate, etc., and blocked isocyanates obtained by reacting a polyisocyanate with a blocking agent such as phenol may also be mentioned.
[0049] As blocked isocyanates, blocked isocyanates prepared by blocking polyisocyanates with a blocking agent can be used. As examples of polyisocyanates, aliphatic diisocyanates such as hexamethylene diisocyanate (including trimers), tetramethylene diisocyanate, and trimethylhexamethylene diisocyanate can be cited; alicyclic polyisocyanates such as isophorone diisocyanate and 4,4'-methylenebis(cyclohexyl isocyanate); aromatic diisocyanates such as 4,4'-diphenylmethane diisocyanate, toluene diisocyanate, and xylylene diisocyanate; modified products of these diisocyanates (carbamates, carbodiimides, uretdiones, uretonimines, biuret and / or isocyanurate modified products, etc.). They can be used alone or in combination of two or more. As examples of end-capping agents, monoalkyl (or aromatic) alcohols such as n-butanol, n-hexanol, 2-ethylhexanol, lauryl alcohol, phenol carbinol, and methyl phenyl carbinol are preferably used; cellosolves such as ethylene glycol monohexyl ether and ethylene glycol mono-2-ethylhexyl ether; polyether-type two-terminal diols such as polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol phenol; polyester-type two-terminal polyols obtained from diols such as ethylene glycol, propylene glycol, and 1,4-butanediol and dicarboxylic acids such as oxalic acid, succinic acid, adipic acid, suberic acid, and sebacic acid; phenols such as p-tert-butylphenol and cresol; oximes such as dimethyl ketoxime, methyl ethyl ketoxime, methyl isobutyl ketoxime, methyl amyl ketoxime, and cyclohexanone oxime; pyrazoles such as dimethyl pyrazole; and lactams represented by ε-caprolactam and γ-butyrolactam. These may be used alone or in combination of two or more.
[0050] Examples of the cationic curing agent include onium compounds represented by amine salts of boron trifluoride, p-methoxyphenyldiazonium hexafluorophosphate, diphenyliodonium hexafluorophosphate, triphenylsulfonium, tri-n-octylphosphine oxide, tetra-n-butylphosphonium tetraphenylborate, tetra-n-butylphosphonium benzotriazolium salt, and tetra-n-butylphosphonium-o,o-diethyldithiophosphate.
[0051] Examples of the phenolic curing agent include novolac phenol and naphthol compounds.
[0052] The content of the flux (E) is 30 to 200 parts by mass, preferably 40 to 180 parts by mass, and more preferably 50 to 160 parts by mass, relative to 100 parts by mass of the binder component. When the content of the flux (E) is 30 parts by mass or more, the conductive paste is easily metallized, and when it is 200 parts by mass or less, excellent conductivity is easily obtained.
[0053] The flux (E) promotes the melting of the low melting point metal particles and integrates them with the high melting point metal particles. Examples of the flux include zinc chloride, lactic acid, citric acid, oleic acid, stearic acid, glutamic acid, benzoic acid, oxalic acid, glutamic acid hydrochloride, aniline hydrochloride, cetylpyridinium bromide, urea, triethanolamine, hydroxyethyl laurylamine, glycerin, hydrazine, 8-ethyloctadecanedioic acid, and rosin.
[0054] The conductive paste of the present invention is obtained by blending predetermined amounts of the above-mentioned components and thoroughly mixing them.
[0055] It should be noted that the conductive paste of the present invention may contain additives that are conventionally added to the conductive paste of the same type within the scope of the purpose of the present invention, and examples thereof include defoamers, thickeners, tackifiers, antioxidants, plasticizers, ultraviolet absorbers, fillers, flame retardants, organic solvents, and the like.
[0056] The viscosity of the conductive paste of the present invention is preferably 50 to 300 Pa·s, more preferably 100 to 250 Pa·s. In this specification, "viscosity" refers to the value measured 1 minute after the start of measurement using a B-type viscometer under the conditions of rotor No. 7, rotation speed 10 rpm, and measurement temperature 25°C.
[0057] The conductive paste of this embodiment is most suitable for filling holes in a multilayer substrate.
[0058] The method for manufacturing the multilayer substrate according to one embodiment of the present invention is not particularly limited, and the multilayer substrate may be manufactured, for example, by the following method. Figure 1 As shown in (a), a prepreg 3 is stacked on a substrate 1 having a through hole 2, and a PET film 4 is stacked thereon. Figure 1 As shown in (b), CO2 laser is irradiated to form through holes 5 in the PET film 4 and the prepreg 3. Figure 1 As shown in (c), the prepreg 3 having the holes 5 formed therein is subjected to plasma treatment. Figure 1 As shown in (d) of FIG. 5 , the hole 5 is filled with a conductive paste 6. Figure 1 As shown in (e), the PET film 4 is peeled off. Figure 1 As shown in (f) of FIG. 8 , the substrate 1 is stacked on the prepreg 3 and heat-pressed in the direction of the arrow to obtain a multilayer substrate 8 .
[0059] The multilayer substrate according to one embodiment of the present invention can also be manufactured by the following method. Figure 2 As shown in (a), PET films 4 are laminated on both sides of the prepreg 3. Figure 2 As shown in (b), CO2 laser is irradiated to form through holes 5 in the PET film 4 and the prepreg 3. Figure 2As shown in (c), a prepreg having holes 5 is placed on a clean room dust-free paper 7, and the holes 5 are filled with a conductive paste 6 (at this time, suction can also be performed from under the clean room dust-free paper). Figure 2 As shown in (d), the PET film 4 is peeled off. Figure 2 As shown in (e) , two substrates 1 are stacked so as to sandwich the prepreg 3, and heat-pressed in the direction of the arrow to obtain a multilayer substrate 8.
[0060] Example
[0061] Examples of the present invention are shown below, but the present invention is not limited to the following examples. In addition, unless otherwise specified, the blending ratio and the like are based on mass.
[0062] The respective components were mixed according to the formulations (parts by mass) shown in Tables 1 and 2 below to prepare conductive pastes.
[0063] Liquid epoxy resin 1: Bisphenol A type epoxy resin, "EP-4400" manufactured by ADEKA Corporation, epoxy equivalent = 200 g / eq
[0064] Liquid epoxy resin 2: NBR-modified epoxy resin, "EPR-1414-1" manufactured by ADEKA Corporation, epoxy equivalent = 400 g / eq
[0065] Solid epoxy resin: phenol novolac type epoxy resin, "JER157S70" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent = 200 g / eq
[0066] High melting point metal particles 1: spherical silver-coated copper powder, average particle size = 5 μm, silver content = 10 mass%, melting point 1073°C
[0067] High melting point metal particles 2: spherical silver powder, average particle size = 5μm, melting point 962℃
[0068] High melting point metal particles 3: spherical silver-coated copper alloy powder, average particle size = 5 μm, silver content = 10 mass%, copper alloy particles containing nickel at a ratio of 5 mass%, melting point 1024°C
[0069] High melting point metal particles 4: flake-shaped silver-coated copper powder, average particle size = 5 μm, silver content = 10 mass%, melting point 1073°C
[0070] Spherical low melting point metal particles: Sn-Bi alloy metal particles (Sn:Bi=42:58, melting point 138°C), average particle size = 5 μm
[0071] Curing agent: Blocked isocyanate curing agent, "CORONATE 2554" manufactured by Tosoh Corporation
[0072] ·Soldering flux: Hydroxyethyl lauryl amine
[0073] The conductivity, adhesive strength, filling property, and reflow resistance of the obtained conductive paste were measured, and the results are shown in Tables 1 and 2. The measurement method is as follows.
[0074] <Conductivity (resistivity)>
[0075] The conductive paste obtained in the examples and comparative examples was line-printed on a glass epoxy substrate using a metal plate (length 60 mm, width 1 mm, thickness about 100 μm), and heated at 180°C for 60 minutes to fully cure, thereby preparing an evaluation substrate having a conductive pattern formed thereon. Next, the resistance value (R) between the two ends of the conductive pattern was measured using a tester, and the cross-sectional area (S, cm 2 ) and length (L, cm) were used to calculate the resistivity using the following formula (1). It should be noted that 5 lines were printed on each of the three glass epoxy substrates to form a total of 15 conductive patterns, and the average resistivity of these patterns was calculated. If the resistivity is less than 1×10 -4 Ω·cm, the conductivity was evaluated to be excellent.
[0076] Resistivity = (S / L) × R (1)
[0077] <Adhesion Strength 1>
[0078] The conductive paste (length 12 mm, width 25 mm, thickness about 100 μm) was printed on a portion of two copper plates (length 100 mm × 25 mm × 1 mm), the pastes were bonded to each other, and heated at 180 ° C for 60 minutes to formally cure them to prepare bonding strength samples. Next, the tensile shear strength was measured using a precision universal testing machine Autograph AGX-V series (manufactured by Shimadzu Corporation). If the shear strength is 5 MPa or more, it is evaluated as excellent bonding strength 1.
[0079] <Adhesion Strength 2: After Thermal Cycle Test>
[0080] After 1000 cycles of heat cycle test of treating the above-mentioned adhesive strength sample at -60°C, 30 minutes and 125°C, 30 minutes, the tensile shear strength was measured, and the change rate of the tensile shear strength before the test was calculated. When the change rate is within ±10%, it is evaluated as excellent in adhesive strength 2 and indicated as "○" in Tables 1 and 2. When the change rate is greater than ±10%, it is evaluated as poor in adhesive strength 2 and indicated as "×" in Tables 1 and 2.
[0081] <Adhesion Strength 3: After Moisture Resistance Test>
[0082] After the above-mentioned adhesive strength sample was left to stand for 1000 hours in an environment of temperature 85°C and humidity 85%, the tensile shear strength was measured, and the change rate of the tensile shear strength relative to that before the test was calculated. When the change rate was within ±10%, it was evaluated as excellent in adhesive strength 3 and indicated as "○" in Tables 1 and 2, and when the change rate was greater than ±10%, it was evaluated as poor in adhesive strength 3 and indicated as "×" in Tables 1 and 2.
[0083] <Filling property>
[0084] The insulating layer (manufactured by Panasonic Corporation, trade name "R-1551") with a thickness of about 100 μm was formed using a CO2 laser. The holes were filled with the conductive paste by printing, and then pressed using a vacuum press under the following pressure and temperature conditions to prepare an evaluation substrate.
[0085] Pressure: 17 minutes from 0kg / cm 2 Increase the pressure to 10.2kg / cm 2 , and maintain for 10 minutes. Then, increase the pressure to 30.6kg / cm2 over 24 minutes. 2 After 46 minutes, it took 23 minutes to reduce the pressure to 0kg / cm 2 .
[0086] Temperature: The temperature was raised from 30°C to 130°C in 17 minutes and maintained for 10 minutes. Then, the temperature was raised to 180°C in 24 minutes, maintained for 46 minutes, and then cooled to 30°C in 23 minutes.
[0087] The hole portion of the evaluation substrate was observed under the following measurement conditions using an X-ray transmission device (trade name "Y.CheetahμHD", manufactured by YXLON International). In the case where there was a portion that was not filled with the paste or cracks occurred during curing, the filling property was evaluated as poor and indicated as "×" in Tables 1 and 2. In the case where no cracks occurred during curing and the paste was fully filled, the filling property was evaluated as excellent and indicated as "○" in Tables 1 and 2.
[0088] <Measurement conditions> Voltage: 50 kV, Current: 80 μA, Power: 4 W
[0089] <Reflow resistance>
[0090] The evaluation substrate produced in the evaluation of filling property was treated in a reflow oven at 260°C for 10 seconds, and this process was repeated 5 times. Then, the hole resistance value was measured, and the rate of change of the hole resistance value of the evaluation substrate before the test was calculated. Regarding the measurement of the resistance value, the resistance value between the two ends of the above-mentioned connection pattern was measured, and the resistance value was divided by the number of holes to obtain the resistance value of each hole, and the average value was calculated. For the samples after the reflow test, the average value of the resistance value was also obtained in the same way. Regarding the rate of change of the resistance value before and after the reflow test, the resistance value measured before the test was set to a, and the resistance value measured after the test was set to b, and the rate of change of the resistance value was calculated by the following formula. When the rate of change is within ±10%, it is evaluated as excellent reflow resistance and is represented as "○" in Tables 1 and 2. When the rate of change is greater than ±10%, it is evaluated as poor reflow resistance and is represented as "×" in Tables 1 and 2.
[0091] Resistance value change rate (%) = (ba) × 100 / a
[0092] [Table 1]
[0093]
[0094] [Table 2]
[0095]
[0096] As can be seen from the results shown in Table 1, Examples 1 to 10 are excellent in electrical conductivity, adhesive strength, filling property, and reflow resistance.
[0097] Comparative Examples 1 and 2 are examples in which the content of the liquid epoxy resin exceeds the upper limit and the content of the solid epoxy resin is less than the lower limit. Comparative Example 1 has poor bonding strength, and Comparative Example 2 has poor bonding strength and reflow resistance.
[0098] Comparative Examples 3 and 4 are examples in which the content of the liquid epoxy resin is less than the lower limit and the content of the solid epoxy resin exceeds the upper limit. Comparative Examples 3 and 4 are inferior in electrical conductivity, filling property, and reflow resistance.
[0099] Comparative Example 5 is an example in which the contents of the high melting point metal particles and the curing agent are less than the lower limits, and the conductivity and the adhesive strength thereof are poor.
[0100] Comparative Example 6 is an example in which the contents of the high melting point metal particles and the flux exceeded the upper limit values, and the bonding strength, filling property, and reflow resistance were poor.
[0101] Comparative Example 7 is an example in which the contents of the low melting point metal particles and the flux are less than the lower limit values, and its bonding strengths 1 and 3 are inferior.
[0102] Comparative Example 8 is an example in which the contents of the low melting point metal particles and the curing agent exceeded the upper limit values, and the bonding strength 1, the filling property, and the reflow resistance were poor.
[0103] Comparative Example 9 is an example in which scaly metal particles are used as high melting point metal particles. The bonding strength 2, filling property, and reflow resistance are poor.
[0104] Description of Reference Numerals
[0105] 1...Substrate
[0106] 2...Through hole
[0107] 3...Prepreg
[0108] 4...PET film
[0109] 5...holes
[0110] 6...Conductive paste
[0111] 7...Cleanroom dust-free paper
[0112] 8...Multilayer substrate
Claims
1. A conductive paste comprising 770 to 4300 parts by mass of spherical high-melting-point metal particles (B) having a melting point of 800° C. or higher, 1510 to 5400 parts by mass of spherical low-melting-point metal particles (C) having a melting point of 240° C. or lower, 10 to 150 parts by mass of a curing agent (D), and 30 to 200 parts by mass of a soldering flux (E), relative to 100 parts by mass of a binder component (A) comprising 5 to 60 parts by mass of a solid epoxy resin and 40 to 95 parts by mass of a liquid epoxy resin in a total amount not exceeding 100 parts by mass.
2. The conductive paste according to claim 1, wherein The spherical high-melting-point metal particles (B) include at least one selected from the group consisting of silver particles, silver-coated copper particles, and silver-coated copper alloy particles.
3. The conductive paste according to claim 1 or 2, wherein The spherical low-melting-point metal particles (C) are composed of an alloy of two or more selected from the group consisting of tin, lead, bismuth, and indium.
4. The conductive paste according to any one of claims 1 to 3, wherein The liquid epoxy resin includes at least one selected from the group consisting of bisphenol epoxy resins, rubber-modified epoxy resins, and glycidyl ether epoxy resins.
5. The conductive paste according to any one of claims 1 to 4, wherein The mass ratio (B) / (C) of the spherical high-melting-point metal particles (B) to the spherical low-melting-point metal particles (C) is 0.25 to 2.
6. A multilayer substrate comprising a plurality of conductive layers and insulating layers interposed between the plurality of conductive layers, wherein holes penetrating the insulating layers are filled with a conductive paste cured material, and the conductive layers in contact with both surfaces of the insulating layers are electrically connected to each other via the conductive paste cured material, The conductive paste cured product is a cured product of the conductive paste according to any one of claims 1 to 5.
Citation Information
Patent Citations
Conductive paste and multilayer board using this
JP2008108629A
Conductive paste
JP2014220238A
Heat hardening type conductive paste composition and cued article thereof
JP2017152221A